Perfil y determinantes microeconómicos de la pobreza en Cartagena de Indias - Elizabeth Torres Rivas; Wilson Guacarí Villalba (Atlantic Review of Economics (ARoEc), 2018)
– The present article aims to analyze the Cartagena de Indias poverty profile and its determinants, which have a direct impact on the probability of a household could be identify as poor or not, through a logistic regression analysis, based on the Logit Binomial model. On the basis of this model, it was necessary to analyze the microeconomic determinants, according to the variables effects related to the household characteristics and the socio - demographic aspects of the head of the household, to know the probability of poverty conditions. This quantitative and analytical approach research is also based on the monetary poverty method in order to identify the poor household, using the Large Integrated Household Survey (GEIH) databases published by the National Administrative Department of Statistics (DANE). It is expected that this study contributes to generate knowledge about the topic as well as to provide useful tools in order to design public policies to combat this conditions. Among the main findings, labor variables and household composition are important to explain the poverty impact. The important of the education is also highlighted, because some aspects such as the head of the household's education level and the household schooling rate are relevant elements to be considered in public policies to reduce poverty in Cartagena de Indias.
Keywords: I32; C51; C53; 330; Poverty Analysis; Determinant Factors; Logistic Regression